2020
DOI: 10.1111/jvp.12896
|View full text |Cite
|
Sign up to set email alerts
|

Serum cannabidiol, tetrahydrocannabinol (THC), and their native acid derivatives after transdermal application of a low‐THC Cannabis sativa extract in beagles

Abstract: Cannabinoids hold promise for treating health problems related to inflammation and chronic pain in dogs, in particular cannabidiol (CBD), and its native acid derivative cannabidiolic acid (CBDA). Information regarding systemic delivery of cannabinoids through transdermal routes is sparse. The purpose of this study was to determine pharmacokinetics of transdermal administration of a low‐THC Cannabis sativa extract in healthy dogs. Six purpose‐bred research beagles were treated with a transdermal CBD‐CBDA‐rich e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 18 publications
1
16
0
Order By: Relevance
“…Found in Cannabis sativa, CBDA is the native acid form, which is converted to CBD during a heat extraction process 11 . Chemical extraction techniques preserve CBDA in the preparation utilized, facilitating absorption from the gastrointestinal tract following oral administration 9,19 . CBDA is known to possess anti-inflammatory and anti-hyperalgesic properties, reducing pain behaviours in a rodent model, which may be superior to those of CBD 20 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Found in Cannabis sativa, CBDA is the native acid form, which is converted to CBD during a heat extraction process 11 . Chemical extraction techniques preserve CBDA in the preparation utilized, facilitating absorption from the gastrointestinal tract following oral administration 9,19 . CBDA is known to possess anti-inflammatory and anti-hyperalgesic properties, reducing pain behaviours in a rodent model, which may be superior to those of CBD 20 .…”
Section: Discussionmentioning
confidence: 99%
“…Further investigations at 2mg/kg dosing of a 50:50 mixture of CBD and CBDA showed superior absorption of a soft chew formulation compared to an oil base, and that administration with food may increase absorption of the active molecules 1,7 . Previous published studies of a similar blend of CBD/CBDA have proven safety and have shown pharmacokinetics of this specific blend as well as other blends of cannabinoids 1,2,6,8,9,10 .…”
Section: Introductionmentioning
confidence: 85%
“…It is worth mentioning that CBD's bioavailability in dogs ob- bioavailability in comparison with the oral route, probably by avoiding hepatic biotransformation (Samara et al, 1988). Hannon et al (2020) have shown that using 4 mg/kg of total cannabinoids twice daily for 2 weeks, given transdermally in a full-spectrum CBD-rich hempextract cream could bypass hepatic metabolism in dogs and deliver systemically and topically CBD and, especially, CBDA and THCA.…”
Section: Methods Of Deliverymentioning
confidence: 99%
“…The intravenous administration of CBD has showed greater bioavailability in comparison with the oral route, probably by avoiding hepatic biotransformation (Samara et al, 1988). Hannon et al (2020) have shown that using 4 mg/kg of total cannabinoids twice daily for 2 weeks, given transdermally in a full ‐ spectrum CBD‐rich hemp‐extract cream could bypass hepatic metabolism in dogs and deliver systemically and topically CBD and, especially, CBDA and THCA. CBD and THC's hepatic metabolism in the dog and in other species involves phase 1 and phase 2 mechanisms (Harvey et al, 1991; De Briyne et al, 2021).…”
Section: Hemp‐based Medicines In Dogs: Clinical Studies and Case Reportsmentioning
confidence: 99%
See 1 more Smart Citation